Analysis of cost of medical therapy in patients of metabolic syndrome: an observational study - Shukla, Prashant; Palta, Shikha; Gupta, Anita; Sehgal, Vijay K. (International Journal of Research in Medical Sciences, 2018)
Background: The objective of the study was to analyze cost of medical therapy in patients of Metabolic syndrome. Methods: This was an observational study. The study was conducted by enrolling patients of the outpatient department of Medicine of Rajindra Hospital, Government Medical College, Patiala, Punjab. A total of 100 patients diagnosed with Metabolic syndrome were enrolled in the study. The total daily cost of the therapy was calculated by adding the direct cost of individual drugs taking in consideration the frequency of the drug. The daily cost of therapy was then extrapolated to calculate the monthly as well as annual cost of therapy. Results: The mean age of patients was 58.27±10.32 years. Out of a total of 100 patients, there were 57 female and 43 male patients, indicating a female preponderance of the disease. The average individual daily cost of medical therapy is INR 44.56 which upon extrapolation gives monthly and annual cost of INR 1336.90 and INR 16264.40 respectively. The cost of treatment in males is costlier than females (INR 50.09 in males versus INR 40.22 in females). The cost of treatment of age 31-40 years is INR 27.90 while it INR 36.97, 48.16 and 50.75 for age groups 41-50, 51-60 and 61-70 years. The various components of metabolic syndrome viz. diabetes mellitus, hypertension and dyslipidemia contribute differently to the cost of therapy. Daily cost of medical therapy for diabetes mellitus is INR 18.57 while for hypertension and dyslipidemia are INR 10.25 and INR 6.13 respectively. Conclusions: Chronic diseases like metabolic syndrome have a huge share of the healthcare budget. Given the fact that it is a lifestyle disease, its prevalence is likely to swell in the coming decades. Hence, formulation of preventive and innovative treatment guidelines is of utmost importance.